2015
DOI: 10.1159/000442283
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's Disease in the Gulf Countries: An Updated Review

Abstract: Background: The Arabian Gulf region is a rapidly developing part of the world. With the increase in average life-expectancy, idiopathic Parkinson's disease (PD), is also expected to increase in prevalence. Furthermore, the high rate of consanguinity among Arabs probably makes familial cases of PD more likely to be encountered than other areas in the world. This review provides an update on the published literature on sporadic and familial PD in Gulf Arabs. Summary: Although the Arab population of this region s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…If this is the case, however, one would expect to find the mutation at high frequencies in other Middle-Eastern Arab countries from where the Islamic conquest descended to Morocco and North Africa. The only studies on the G2019S mutation in Arab countries have come recently from Egypt, which reported a frequency among sporadic PD patients of 9.7% (11/113) in the north [29] and only 1.45% (1/69) in the South of the country [30], and also from Saudi Arabia and all Gulf countries where the mutation was reported to be absent [31,32]. Together, these data suggest that it is highly unlikely that the mutation is of Arabic origin.…”
Section: Discussionmentioning
confidence: 99%
“…If this is the case, however, one would expect to find the mutation at high frequencies in other Middle-Eastern Arab countries from where the Islamic conquest descended to Morocco and North Africa. The only studies on the G2019S mutation in Arab countries have come recently from Egypt, which reported a frequency among sporadic PD patients of 9.7% (11/113) in the north [29] and only 1.45% (1/69) in the South of the country [30], and also from Saudi Arabia and all Gulf countries where the mutation was reported to be absent [31,32]. Together, these data suggest that it is highly unlikely that the mutation is of Arabic origin.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, an estimation of approximately 2.4 million people are diagnosed with epilepsy each year [14]. Parkinson's disease (PD) is reported to be common among the elderly [15]. Due to the high rate of people living with brain diseases, there is a need for the development of effective therapeutics that can penetrate the BBB.…”
Section: Introductionmentioning
confidence: 99%
“…These central nervous system (CNS) neurons are used as primary neurotransmitter dopamine, which is responsible for transmitting the necessary information for the correct control of movements [ 1 , 2 ]. It is considered the most frequent neurodegenerative disease after Alzheimer's disease and the most common movement disorders [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%